1982
DOI: 10.2307/3281094
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum: Modifications of the In vitro Culture Conditions Improving Parasitic Yields

Abstract: We attempted to optimize some of the variables involved in the in vitro culturing of Plasmodium falciparum. Irrespective of the isolates used, suspension cultures in glucose-enriched RPMI-1640 medium buffered with TES yielded about twice the amount of parasites than could be obtained from static, thin-layer cultures with HEPES-buffered RPMI-1640 without additional glucose. In suspension cultures, methylcellulose (1 mg/ml) was added to protect the erythrocytes. In addition the erythrocytes were found to be more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…Mosquitoes were reared at 27°C and 80% humidity on a 12-h light to dark cycle under standard laboratory conditions. The four P. falciparum strains used (NF54, 3D7, GB4 and 7G8) were maintained in O+ human erythrocytes using RPMI medium 1640 supplemented with 25 mM Hepes, 50 mg/L hypoxanthine, 25 mM NaHCO3, and 10% (vol/vol) heat-inactivated type O+ human serum at 37°C and a gas mixture of 5% O 2 , 5% CO 2 , and balance N 2 (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Mosquitoes were reared at 27°C and 80% humidity on a 12-h light to dark cycle under standard laboratory conditions. The four P. falciparum strains used (NF54, 3D7, GB4 and 7G8) were maintained in O+ human erythrocytes using RPMI medium 1640 supplemented with 25 mM Hepes, 50 mg/L hypoxanthine, 25 mM NaHCO3, and 10% (vol/vol) heat-inactivated type O+ human serum at 37°C and a gas mixture of 5% O 2 , 5% CO 2 , and balance N 2 (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Mosquitoes were reared at 27°C and 80% humidity on a 12-h lightdark cycle under standard laboratory conditions. The Plasmodium falciparum strains used-NF54, SenTh015.04 (MRA-1181) from Senegal, 7G8 from Brazil, IPC 3445 Pailin Cambodia 2010 (MRA-1236), IPC 4912 Mondolkiri Cambodia 2011 (MRA-1241), NF54-Pfs47KO and Pfs47KO complemented lines (Pfs47 Africa-Nf54, Pfs47 Asia MRA-1241, and Pfs47 America-7G8)-were maintained in O+ human erythrocytes using RPMI medium 1640 supplemented with 25 mM Hepes, 10 mg/L hypoxanthine, 25 mM NaHCO 3 , and 10% (vol/vol) heat-inactivated type O+ human serum (Interstate Blood Bank) at 37°C and with a gas mixture of 5% O 2 , 5% CO 2 , and balance N 2 (28,29). Tables S3 and S4).…”
Section: Methodsmentioning
confidence: 99%
“…Suspension cultures of parasites have also been tried. Zolg et al (100) reported improved yields with shaking of cultures, but these claims have been disputed (39). Fragility of the infected red blood cells is an important factor in agitated cultures, but this has been countered to some extent by the use of methylcellulose in agitated cultures (47, 100).…”
Section: Erythrocytic Stagesmentioning
confidence: 99%